Description of the development and validation of the Canadian Paediatric Trigger Tool. Issue 5 (17th January 2011) - Matlow, Anne G; Cronin, Catherine M G; Flintoft, Virginia; Nijssen-Jordan, Cheri; Fleming, Mark; Brady-Fryer, Barbara; Hiltz, Mary-Ann; Orrbine, Elaine; Baker, G Ross
Abstract : Objective: To describe the process of developing and validating the Canadian Association of Paediatric Health Centres Trigger Tool (CPTT). Methods: Five existing trigger tools were consolidated with duplicate triggers eliminated. After a risk analysis and modified Delphi process, the tool was reduced from 94 to 47 triggers. Feasibility of use was tested, reviewing 40 charts in three hospitals. For validation, charts were randomly selected across four age groups, half medical/half surgical diagnoses, from six paediatric academic health sciences centres. 591 charts were reviewed by six nurses (for triggers and adverse events (AEs)) and three physicians (for AEs only). The incidence of trigger- and AE-positive charts was documented, and the sensitivity and specificity of the tool to identify charts with AEs were determined. Identification of AEs by nurses and physicians was compared. The positive predictive value (PPV) of each trigger was calculated and the ratio of false- to true-positive AE predictors analysed for each trigger. Results: Nurses rated the CPTT easy to use and identified triggers in 61.1% (361/591; 95% CI 57.2 to 65.0) of patient charts; physicians identified AEs in 15.1% (89/ 591, 95% CI 0.23 to 0.43). Over a third of patients with AEs were neonates. The sensitivity and specificity were 0.88 and 0.44, respectively. Nurse and physician AE assessments correlated poorly. The PPV for each trigger ranged from 0 to 88.3%. Triggers with a false/true-positive ratio of >0.7 were eliminated, resulting in the final 35-trigger CPTT. Conclusions: The CPTT is the first validated, comprehensive trigger tool available to detect AEs in children hospitalised in acute care facilities.